2017
DOI: 10.1186/s40360-017-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

The albumin-exendin-4 recombinant protein E2HSA improves glycemic control and β-cell function in spontaneous diabetic KKAy mice

Abstract: BackgroundE2HSA is a genetic fusion protein that consists of two tandem exendin-4 molecules that are covalently bonded to recombinant human serum albumin via a peptide linker. Previous studies have demonstrated that E2HSA significantly decreased blood glucose levels, improved β-cell function and promoted β-cell proliferation in diabetic db/dB mice. This study aimed to evaluate the benefits of E2HSA on glucose and lipid metabolism in a spontaneous diabetes animal model, KKAy mice.MethodsE2HSA was acutely admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These results were consistent with those of previous reports on the characteristic features of KKAy mice [12].…”
Section: Resultssupporting
confidence: 94%
“…These results were consistent with those of previous reports on the characteristic features of KKAy mice [12].…”
Section: Resultssupporting
confidence: 94%
“…GLP-1 is one of the most central mediators of glycemic control after gastric bypass in diabetic patients (18). Exendin-4 is a GLP-1 analogue and not inactivated by dipeptidyl peptidase-4, which has an incretin effect, controls blood glucose and protects islet β cells (19,20), but its specific mechanism of action remains unclear. Previous findings have shown that improving pancreatic inflammation and fibrosis and changing microRNA expression level in the pancreatic tissue and blood, Exendin-4 intervention in NOD mice upregulates miR-1 level, downregulates miR-19a, miR-19b and miR-22 levels and inhibits the differentiation and maturation of islet β cells, as well as promotes the recovery of insulin secretion function (21).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the glucose and protein content were determined using NobiStrip U10 test stripes (HI-309-38810601, Hitado) according to the manufacturer's instructions. For determining blood glucose levels, mice were fasted for 4 h 19,20 with water ad libitum, blood samples were taken by puncture of a tail vein and immediately analyzed using Accu-Chek Aviva Connect (PZN 11532906, Roche Diabetes Care). The concentrations of the urinary elecrolytes (sodium, chloride, glucose, and urea) as well as the osmolality were measured according to the manufacturer's instructions (Roche Diagnostics, Cobas c501 module).…”
Section: Urine Measurementsmentioning
confidence: 99%